2013
DOI: 10.1080/00224499.2012.719168
|View full text |Cite
|
Sign up to set email alerts
|

Pornography Actresses: An Assessment of the Damaged Goods Hypothesis

Abstract: The damaged goods hypothesis posits that female performers in the adult entertainment industry have higher rates of childhood sexual abuse (CSA), psychological problems, and drug use compared to the typical woman. The present study compared the self-reports of 177 porn actresses to a sample of women matched on age, ethnicity, and marital status. Comparisons were conducted on sexual behaviors and attitudes, self-esteem, quality of life, and drug use. Porn actresses were more likely to identify as bisexual, firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1
22

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 32 publications
1
7
1
22
Order By: Relevance
“…wrestling, American football, rugby) seem to be a vulnerable group [18]. Furthermore, with 13.7% of the deceased actors in our study found to be in the pornographic film industry, our data support the findings of earlier authors who found an increased likelihood for drug abuse in male and female porn actors [19, 20]. …”
Section: Discussionsupporting
confidence: 90%
“…wrestling, American football, rugby) seem to be a vulnerable group [18]. Furthermore, with 13.7% of the deceased actors in our study found to be in the pornographic film industry, our data support the findings of earlier authors who found an increased likelihood for drug abuse in male and female porn actors [19, 20]. …”
Section: Discussionsupporting
confidence: 90%
“…As sex work research tends to focus on the problematic aspects of it, these intrinsic motivations and positive experiences tend to stay under the radar. That sex work is not necessarily a negative experience is also suggested by a recent study with 177 porn actresses which found that these women did not report poorer well‐being compared to a matched comparison group (Griffith et al ). In our study a range of negative experiences were also mentioned, however, broadly covering the stressful nature of the work itself (potentially unpleasant customers, fear of violence), its psychological consequences (for self‐esteem and attitudes toward sex), its social consequences (the stigma attached to it which drives negative judgement from friends and family and concomitant secrecy) and the socio‐legal employment context within which the work is embedded (e.g.…”
Section: Discussionmentioning
confidence: 73%
“…Other studies related to pornographic films mostly focus on the explorations that viewers may have caused sexual risk behaviours (Tadesse & Yakob, 2015) and subsequent sexually transmitted diseases (Mahapatra & Saggurti, 2014). For pornography actress production, there are few studies addressing related issues, such as the effects of pornography consumption on U.S. males in Wright (2013) and on gender equality in Baron (1990), and the damaged goods hypothesis on female performers in Griffith, Mitchell, Hart, Adams, and Gu (2013). In an empirical study of the A.V.…”
Section: Development Of the Av Industrymentioning
confidence: 99%